Negative Impact of Sigma-1 Receptor Agonist Treatment on Tissue Integrity and Motor Function Following Spinal Cord Injury - Alise Lattard; Gaëtan Poulen; Gaëtan Poulen; Sylvain Bartolami; Yannick N. Gerber; Florence E. Perrin; Florence E. Perrin (Frontiers Media S.A., 2021)
In traumatic spinal cord injury, the initial trauma is followed by a cascade of impairments, including excitotoxicity and calcium overload, which ultimately induces secondary damages. The sigma-1 receptor is widely expressed in the central nervous system and is acknowledged to play a key role in calcium homeostasis. Treatments with agonists of the sigma-1 receptor induce beneficial effects in several animal models of neurological diseases. In traumatic injury the use of an antagonist of the sigma-1 receptor reversed several symptoms of central neuropathic pain. Here, we investigated whether sigma-1 receptor activation with PRE-084 is beneficial or detrimental following SCI in mice. First, we report that PRE-084 treatment after injury does not improve motor function recovery. Second, using ex vivo diffusion weighted magnetic resonance imaging completed by histological analysis, we highlight that σ1R agonist treatment after SCI does not limit lesion size. Finally, PRE-084 treatment following SCI decreases NeuN expression and increases astrocytic reactivity. Our findings suggest that activation of sigma-1 receptor after traumatic spinal cord injury is detrimental on tissue preservation and motor function recovery in mice.